Two 2MASS-selected Young Stellar Clusters: Photometry, Spectroscopy, and the Initial Mass Function - Leistra, A; Cotera, A. S; Liebert, J; Burton, M (The Astronomical journal, 2005)
We present near-IR (NIR) J, H, and Ks images and K-band spectroscopy of two newly discovered stellar clusters at different stages of evolution. Our spectra suggest the presence of massive young stellar objects in the heavily embedded cluster in the star-forming region near radio source G353.4-0.4 and an O5-O6 V star in the cluster near radio source G305+00.2. We determine a K-band luminosity function (KLF) for both clusters and an initial mass function (IMF) for the cluster near G305+00.2. The derived IMF slope is = -1.5 if the KLF is used to derive the IMF and is = -0.98 if the color-magnitude diagram (CMD) and spectra are used. The more reliable CMD-based slope is flatter than the Salpeter value usually found for stellar clusters. We find that using the KLF alone to derive an IMF is likely to produce an overly steep slope in stellar clusters subject to variable extinction.